Study on mathematical model of coal particles gas adsorption under different particle sizes and pressures - GAO Yu, LIU Jia, QIN Yueping (Meikuang Anquan, 2023)
Gas adsorption experiment with coal particles is a basic means to study the gas flow mechanism of coal matrix. In order to explore the influence of coal particle shape on coal gas adsorption law, a constant temperature and pressure adsorption experiment was designed to obtain the adsorption characteristics of coal samples with four particle sizes under different gas pressures. Based on the gradient diffusion theory of free gas density in coal matrix, the mathematical models of constant pressure adsorption of cylindrical and spherical coal gas were established respectively, and solved by finite difference method, and the simulation results were verified by experimental data. It is found that the simulation results obtained by considering the coal particles as spherical or cylindrical have a good match with the experimental results, which proves the accuracy and reliability of the gradient diffusion theory of free gas density in coal matrix. The diffusion coefficient increases with the increase of coal particle size. The influence of gas adsorption pressure on the diffusion coefficient of micropore is small, and the diffusion coefficient of difference of surface area between the two shapes.